1997
DOI: 10.1111/j.1365-3032.1997.tb01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Juvenile Hormone biosynthesis and degradation during reproductive development and diapause in the boll weevil, Anthonomus grandis

Abstract: Abstract. The role of Juvenile Hormone (JH) during reproductive development and diapause was investigated in the boll weevil, Anthonomus grandis Boheman (Coleoptera: Curculionidae). JH sythesized by corpora allata (CA) in vitro of A.grandis was identified as JH‐UJ by high‐performance liquid chromatography and by conversion to the methoxyhydrin. Optimal conditions for the use of a short‐term assay in vitro were established to examine profiles of CA activity. In addition, rates of JH degradation by JH‐specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Surprisingly, low levels of AgraVg transcripts were detected in eggs, larval and pupal stages. Other work did not mention the presence of either AgraVg transcripts or proteins in other stages than adult female in A. grandis ( Taub-Montemayor et al, 1997a , Taub-Montemayor et al, 1997b , Taub-Montemayor and Rankin, 1997 ). Only very low transcript amounts were detected in comparison to adult females, representing maybe just basal transcription ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, low levels of AgraVg transcripts were detected in eggs, larval and pupal stages. Other work did not mention the presence of either AgraVg transcripts or proteins in other stages than adult female in A. grandis ( Taub-Montemayor et al, 1997a , Taub-Montemayor et al, 1997b , Taub-Montemayor and Rankin, 1997 ). Only very low transcript amounts were detected in comparison to adult females, representing maybe just basal transcription ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Phillips (1976) opined that some weevils were already in a state of diapause at the time of adult emergence, although he provided no supporting experimental evidence. Taub-Montemayor et al (1997) produced putative diapausing weevils by exposing unfed newly-emerged weevils to a photoperiod of 12:12 h and a thermoperiod of 26:21°C [L:D], but none of the weevils survived beyond 10 d. Finally. Spurgeon and Raulston (1998a) and Spurgeon and Esquivel (2000) found that feeding regimen could be manipulated to control the diapause response, and their techniques were used to produce high levels of overwintering survival (45-73%) in field studies (Westbrook et al 2003), and to identify and characterize a storage protein diagnostic of diapause in boll weevils (Lewis et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, decapitation of females after emergence resulted in the failure of production of mature oocytes in Spodoptera frugiperda (Sorge et al 2000). A positive correlation between JH synthesis and ovarian development has been reported in several species of Coleoptera (Kramer, 1978; Guan and Chen, 1986; Taub-Montemayor, et al 1997), except in the mealworm beetle, Tenebrio molitor (Weaver et al 1978). Although germ-cell cluster formation in the ovary has been studied in the larval and pupal stages of the red flour beetle, Tribolium castaneum (Trauner and Buning, 2007), the endocrine and molecular mechanisms underlying the beetle oocyte maturation in the adult stage remain unknown.…”
Section: Introductionmentioning
confidence: 93%